A high gain pifa at 2.45 GHz and 5.8 GHz using wireless power transfer techniques for pacemaker application - Logendran, V. (Asian Research Publishing Network, 2016)
The design of a high gain Planar Inverted F Antenna (PIFA) with two different frequencies for medical pacemaker is presented. Two PIFA designs have been optimized to be operated at ISM band of 2.45 GHz and 5.8 GHz respectively, under tolerable reflection coefficient of less than -10dB. Both of the proposed antennas are developed from copper plate with a simple structure of rectangular patch. All design and simulation has been carried out using Computer Simulation Technology (CST) Microwave Studio Suite. The simulated and measured results of the fabricated antenna on reflection coefficient, bandwidth radiation pattern, and gain are presented to validate the usefulness of the presented design. The 2D Anechoic Chamber and Agilent Technologies Network Analyzer have been used for the measurement. Both 2.45 GHz and 5.8 GHz antennas have successfully manage to achieve high gain of 6dB and 8.2dB respectively with a directional beam pattern. The presented ISM PIFAs could be potential for point-to-point communication using wireless power transfer technique for medical pacemaker application.